2019
DOI: 10.3390/buildings9030067
|View full text |Cite
|
Sign up to set email alerts
|

Corroded RC Beams at Service Load before and after Patch Repair and Strengthening with NSM CFRP Strips

Abstract: This paper presents the experimental results of the structural behavior of four reinforced concrete beams with corroded steel reinforcement at service loads. One beam was non-corroded, one beam was corroded under an accelerated electrochemical technique to a small corrosion level (for one corrosion cycle), while two beams were corroded under the same conditions of an accelerated electrochemical technique and then subjected to vertical service loads that corresponded to 60% and 75% of the yield load of the non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…The Crisafulli model [32] is extensively used for masonry infilled panels and implemented in the SeismoStruct software used in this simulation. The RC beams in the buildings were assumed to be noncorroded beams, so there was no need to replace the cracked concrete substrate with high-strength polymer-modified cementitious mortar before strengthening [33].…”
Section: Retrofitting Asymmetric Reinforced Concrete Frame Buildings: a Worst-case Scenariomentioning
confidence: 99%
“…The Crisafulli model [32] is extensively used for masonry infilled panels and implemented in the SeismoStruct software used in this simulation. The RC beams in the buildings were assumed to be noncorroded beams, so there was no need to replace the cracked concrete substrate with high-strength polymer-modified cementitious mortar before strengthening [33].…”
Section: Retrofitting Asymmetric Reinforced Concrete Frame Buildings: a Worst-case Scenariomentioning
confidence: 99%
“…The soil condition is an essential component that must be addressed for FRP piles because piles are used to support massive constructions, yet most of the works discussed over FRP piles and do not include soil effects. In reality, there are fewer studies on FRP heaps than on traditional piles [30][31][32][33][34][35][36], and even fewer studies evaluate the influence of soil when examining FRP piles. The research among FRP piles with varying load regimes is not necessary, leaving a gap [35].…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that using steel plates to strengthen corroded beams enhanced both load‐carrying capacity and ductility. Triantafyllou et al 31 studied experimentally the performance of corroded RC beams strengthened with near‐surface mounted (NSM) CFRP plate. In general, the results showed that the failure load of corroded beams improved due to the use of the NSM strengthening system.…”
Section: Introductionmentioning
confidence: 99%